Digitalization of Energy Manufacture: Infrastructure, Supply Chain Strategy and Communication - Valentin Y. Afanasyev; Natalia G. Lyubimova; Vladimir F. Ukolov; Salavat R. Shayakhmetov (International Journal of Supply Chain Management, 2019)
Abstract- The constant development of the electric power industry today leads to a decrease in the sustainability and growth of accidents in the â€œUES of Russiaâ€, necessitates the adoption of operational and supply chain management decisions that are not possible without digitalization. The problems that the industry will face in implementing digitalization projects are identified, namely: increased equipment wear; lack of funding, requirements for technological compatibility of the characteristics and parameters of power equipment and devices, unified switching standards (protocols) and information models, required number of instruments, equipment and software. Despite the obvious problems, digitalization is being actively implemented in the power industry. It is noted that the target model of digitalization in the power industry should include three blocks: digital technologies and databases, information technology infrastructure, including communication channels, information security systems. The spheres of application of existing and future digital technologies and databases at all stages of energy production are considered: generation, power grids, sales activities, in their relationship with the management bodies of the wholesale and retail electricity and capacity markets and regulatory bodies. The possibilities of using own and leased communication channels are critically evaluated, the advantages of various communication channels are revealed. It is noted that it is necessary to use channels based on fiber-optic communication lines as the main ones, and satellite communication channels as reserve ones. Special attention is drawn to information security. The components of the effect of digitalization for consumers, energy companies and the state are determined. It is proposed to introduce integrated indicators of the effect of digitalization. The proposed measures are necessary for the implementation of full-scale digitalization of the power industry, including the preservation of savings from digitalization in power companies, government support, and the creation of conditions for the development of active consumers.